Pengaruh Kepercayaan, Kemudahan dan Kualitas Layanan Terhadap Kepuasan Nasabah (Studi pada Pengguna M-Banking Bank BRI di Kota Malang) - Firdaus, Hilda Alivia; Nurhidayah, Nurhidayah; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this study is to test and analyze the influence of trust (X1), convenience (X2)  and service quality (X3) on customer satisfaction in Bank BRI m-banking users in Malang City. The type of research used is explanatory research with a quantitative approach. The population of this study is Bank BRI customers in Malang City who use the BRImo application. The sample of this study used the Malhotra formula, which was obtained from a sample of 90 respondent. This study uses a multiple linear regression analysis method, which is carried out using the SPSS 25 analysis program. The result of this study show that the Trust variable (X1) has no effect on customer satisfaction in Bank BRI m-banking users in Malang City, the Convenience variable (X20 has an effect on customer satisfaction in Bank BRI m-banking users in Malang City and the Service Quality variable (X30 has an effect on customer satisfaction in Bank BRI m-banking users in Malang. City. Keywords: Turst, Convenience, Service Quality, Customer Satisfaction